Revitalisasi Baitul Maal Wat Tamwil sebagai Pilar dalam Meningkatkan Perekonomian Masyarakat - Dede Khoirunnisa; Heni Noviarita; Evi Eka Elvia (Media of Law and Sharia, 2023)
This research discusses the revitalization of Baitul Maal Wat Tanwil (BMT) as a pillar in improving the community's economy. The focus of the research examines solving economic problems by knowing the basics of improving the community's economy through Baitul Maal Wat Tanwil (BMT). The research method used is normative research, by explaining the problems of Baitul Maal Wat Tanwil (BMT) through data associated with the legal basis of the underlying statutory law. The data sources in this study were taken from BMT-related institutions and described using narration. The results of research in this study, namely that Qardhul Hasan financing, is very helpful for people who want to develop their business by borrowing capital funds from BMT institutions without worrying about additional payments (usury). ). Baitul Maal Wat Tanwil (BMT) has a message as a means to avoid non-Islamic economic transactions, encourage economic activity in small business capital, avoid borrowing from moneylenders, and maintain community economic stability.